THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL COMMITMENTS ON EMPLOYEE PERFORMANCE IN CV ARTHA MEGA MANDIRI MEDAN - Erina , Erina (Journal of Industrial Engineering & Management Research, 2021)
To increase employee performance, many factors influence it, but in this research it is necessary to find the effect of increasing employee performance from transformational leadership styles and organizational commitment. This research was conducted at CV Artha Mega Mandiri Medan, with respondents being employees, a sample of 100 people was taken using stratified random sampling technique. The data were processed using SPSS 25 to find the effect with multiple regression and correlation. The results show that there is a positive and significant influence between transformational leadership style and employee performance by 75%. Keywords: Transformational Leadership, Organizational commitment, and employee performance